1). 5√2 pe 2√5- 3 pe √10. 2). (√2+3pe √2):(√2)totu la -1. 3). 3•(3 1pe 2-1,25•2)-(√5-2,5pe √5)•√5
Răspunsuri la întrebare
Răspuns de
2
1). 5√2/2√5- 3/√10=
=5√2*√5/2√5*√5- 3*√10/√10*√10=
=5√10/10- 3√10/10=
=2√10/10=√10/5
2). (√2+3/√2):(√2)⁻¹ =
= (√2+3√2/2):(1/√2) =
=(2√2+3√2)/2 x √2=
=5√2/2 x √2=
=5*2/2=
=5
3). 3•(3 1/2-1,25•2)-(√5-2,5/√5)•√5=
= 3•(3,5-2,5)-(5-2,5)=
= 3•1-2,5=0,5
=5√2*√5/2√5*√5- 3*√10/√10*√10=
=5√10/10- 3√10/10=
=2√10/10=√10/5
2). (√2+3/√2):(√2)⁻¹ =
= (√2+3√2/2):(1/√2) =
=(2√2+3√2)/2 x √2=
=5√2/2 x √2=
=5*2/2=
=5
3). 3•(3 1/2-1,25•2)-(√5-2,5/√5)•√5=
= 3•(3,5-2,5)-(5-2,5)=
= 3•1-2,5=0,5
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă